Corrugation profile effect on heat transfer enhancement of laminar flow region - Mohd. Jaafar, Mohammad Nazri (2015)
Corrugations for Enhancement of heat transfer surface are used in many engineering applications such as heat exchanger, air conditioning and refrigeration systems. Many techniques have been investigated on the enhancement of heat transfer rate in order to reduce the size and cost of the required equipment especially in the design of heat exchangers. One of the most important methods used is a passive heat transfer technique. This method when employed in the heat exchanger showed that the overall thermal performance improved significantly. Computational Fluid Dynamics (CFD) simulation of heat transfer and fluid flow analysis in a laminar flow regime in spirally corrugated tubes with horizontal orientation are presented in this paper. Constant wall heat flux condition was applied with water as a working fluid. At Reynolds number range of 100-1300, spirally corrugated tubes were examined and the results are compared to the standard smooth tube. Results shows that heat transfer enhancement in the range of (18.4-36.3) % have been achieved.